Evaluations of the physiological parameters of pregnant mice under chronic stress conditions - Miranda, Evelyn Fernandes de; Carneiro, Verônica Santos Martins; Guimarães, Geovana Iasmim Silva; Silva, Weslane Amorim do Carmo; Barbosa, Tiago Souza; Queiroz, Cindy santos de; Rocha, Marilene Lopes da; Duarte, Rosângela Rodrigues (Seven Editora, 2024)
Chronic stress can cause significant changes in the behavior and organ functions of organisms exposed to stressful conditions. Currently, the concept of stress is defined as a disturbance of homeostasis resulting from environmental, physiological, and psychological influences. In this context, this study aimed to investigate the physiological effects on pregnant females subjected to stressful conditions. The research was conducted at the Laboratory of Neuropsychopharmacology at the Central Vivarium of the University of Feira de Santana, Bahia. A total of 12 adult Mus musculus mice were used, 8 females and 4 males. After mating, females were divided into four distinct groups, with 2 females in each: light cycle, social isolation, overcrowding, and control. For 19 days, 02 females were kept under the same stress conditions previously established, so weight, waist circumference, heart and respiratory rates were monitored. The data were recorded in Excel and the graphs were generated using Sigma Plot. The results indicated that the stressful conditions influenced the physiological aspects of the groups, including affecting weight. It was observed that the groups subjected to stress presented more physiological variations compared to the control group. Studies that aim to understand the effects of stress on the physiological aspects of animal species are of paramount importance, as they can provide relevant insights into the possible impacts of a stressful pregnancy on children and adolescents. Although this study is preliminary, the results are promising in showing that stress during pregnancy underscores the importance of providing a quiet environment for fetal development. It is expected that these results will contribute significantly to the advancement of knowledge in this area and may have important implications, especially when investigating the behavioral and physiological aspects of offspring born to mothers exposed to stress during pregnancy. DOI:https://doi.org/10.56238/sevened2024.007-026